The contribution of ethical reflection during the Coronavirus pandemic. A comparative analysis. - Picozzi, Mario; Severgnini, Paolo (Medicina Historica, 2020)
The Coronavirus pandemic has deeply marked all ordinary health care activities and has dictated matters usually faced by the medicine of disasters. The most critical and dramatic dilemma has been the triage and the urge to select patients for Intensive Care Unit (ICU) because there was no place for all at the same time. The need to decide in a very short time has made this decision even more complex. The data of the Italian situation and namely of Lombardia reveal it clearly. Worldwide, there have been many different views on triage, sometimes with very peculiar emphasis. In this paper we will illustrate the contributions of the Unites States compared to the European ones. We have operated a choice among many articles and guide lines about this matter, and we have prioritized those most quoted in literature. We have critically analyzed different views and we have highlighted that nevertheless there are several shared elements such as clinical criteria, if we consider only them we might underestimate the uniqueness of the patient, including vulnerable ones. There is a huge gap between the US view and the European view when it comes to the appointment of the final decision maker in triage. We propose the criteria of proportionality as a guide line to take decisions in triage because it allows to integrate collective public health objectives and the principle of ensuring protection for the individual patient. Finally, we envisage the potential role of ethics consultation in this pandemic scenario.